2019
DOI: 10.2196/10117
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Acceptance of mHealth in Patients With Cardiovascular Diseases: A Cross-Sectional Study

Abstract: Background Mobile health (mHealth)—a method of assisting long-term care in patients with chronic cardiovascular diseases (CVDs)—is gaining popularity in China, mainly owing to the large number of patients and limited clinical resources. Patients of different ages have varying needs for CVD management. However, evidence regarding how age influences Chinese CVD patients’ use and perceptions of mHealth is limited. Objective This study aimed to explore age-related differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 15 publications
3
25
0
13
Order By: Relevance
“…It is likely that those with greater levels of education have greater self-efficacy for finding information online or are possibly exploring alternative knowledge sources beyond their health care providers. Moreover, lower levels of health technology acceptance [72,73] and eHealth literacy [74,75] among high school graduates may also partially explain this finding.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that those with greater levels of education have greater self-efficacy for finding information online or are possibly exploring alternative knowledge sources beyond their health care providers. Moreover, lower levels of health technology acceptance [72,73] and eHealth literacy [74,75] among high school graduates may also partially explain this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the relationship between the incidence rate of MetS and its risk factors such as smoking, drinking, physical activity, depression, and environmental and demographic factors [ 18 ]. Moreover, one study revealed that an unhealthy daily lifestyle increases the risk of cardiocerebrovascular diseases and that improved habits act as preventive measures [ 19 ]. Further, the Third Report of the National Cholesterol Education Program Expert Panel in Europe reported that it is important to identify patients with MetS and treat them to prevent cardiocerebrovascular diseases [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous practice areas outside pediatrics utilize mHealth address adherence, including mHealth adherence. Prominent among these areas are the use of technologies to communicate during the management of adult cardiac disease, lung disease, transplantation, diabetes mellitus, and other chronic medical conditions (Devito Dabbs et al, 2009; Hamine et al, 2015; Jiang et al, 2019; Shaw et al, 2016; Subhi et al, 2015). In long‐term therapies, factors related to the patient, medical condition, treatment, socioeconomic status, and healthcare team have all been associated with levels of adherence (Sabate, 2003).…”
Section: Resultsmentioning
confidence: 99%